2023
DOI: 10.1155/2023/2516472
|View full text |Cite|
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Mitigates Oxidative Stress and Mitochondrial Damages Induced by Polystyrene Microplastics in Osteoblastic Cells of Mice

Abstract: Polystyrene microplastics (mic-PS) have become harmful pollutants that attracted substantial attention about their potential toxicity. Hydrogen sulfide (H2S) is the third reported endogenous gas transmitter with protective functions on numerous physiologic responses. Nevertheless, the roles for mic-PS on skeletal systems in mammals and the protective effects of exogenous H2S are still indistinct. Here, the proliferation of MC3T3-E1 cell was analyzed by CCK8. Gene changes between the control and mic-PS treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%